1986
DOI: 10.1016/0266-7681(86)90164-6
|View full text |Cite
|
Sign up to set email alerts
|

Joint reconstruction following trauma: Comparison of microsurgical transfer and conventional methods: A report of 61 cases

Abstract: Joint reconstruction at the metacarpophalangeal or proximal interphalangeal levels remains a difficult problem in hand surgery. The authors reviewed sixty-one joints reconstructed acutely or electively allowing to compare Swanson spacer (30 joints), interpositional arthroplasty (4), non vascularized joint transfer (5) and vascularized joint transfer (21). Among these, two different techniques have been used: island compound transfer from a finger bank (10) and free vascularized transfer from the second toe (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
7

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 7 publications
1
23
0
7
Order By: Relevance
“…A variety of surgical strategies have been employed for the repair of joint chondral lesions, including drilling, abrasion arthroplasty, and microfracture to promote 17 In addition, although some authors have reported resorption, joint space narrowing, and avascular necrosis with large grafts, 18,19 osteochondral grafts have been used in hand surgery, particularly for small joint reconstruction. 8,9,20,21 Several treatment options have also been reported for finger joint reconstruction with acceptable results.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of surgical strategies have been employed for the repair of joint chondral lesions, including drilling, abrasion arthroplasty, and microfracture to promote 17 In addition, although some authors have reported resorption, joint space narrowing, and avascular necrosis with large grafts, 18,19 osteochondral grafts have been used in hand surgery, particularly for small joint reconstruction. 8,9,20,21 Several treatment options have also been reported for finger joint reconstruction with acceptable results.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is nonetheless a technically demanding procedure and creates substantial donor site defects, and thus it is generally reserved for the most severe forms of compound loss or for children with an open physis. 14 The authors present 3 cases of posttraumatic destruction of the proximal interphalangeal joint treated by an alternative resection arthroplasty technique that includes collateral ligament reconstruction for lateral stability, tendon interposition for articulation, and volar tenodesis to prevent hyperextension.…”
mentioning
confidence: 99%
“…La plupart ont déjà disparu et force est de constater que la prothèse efficace et durable reste à découvrir !! ; les transferts articulaires non vascularisés sont tombés en désuétude à cause des mauvais résultats dus à la disparition constante du cartilage et de l'os sous-chondral[17] ; les transferts vascularisés libres ou en îlot maintiennent la vascularisation indispensable à la survie de l'articulation transférée et à la production de liquide synovial. Le développement des lambeaux et l'avènement de la microchirurgie a permis toutes les expérimentations de reconstruction articulaire à partir du pied ou de la main.…”
unclassified
“…Malheureusement, les résultats fonctionnels médiocres associés à la difficulté technique de ces interventions font qu'elles restent d'indication exceptionnelles. Il n'en demeure pas moins que dans certains cas bien ciblés, les transferts articulaires pédiculés au niveau des doigts peuvent transformer l'avenir fonctionnel du patient[10,17].Si l'indication d'un transfert hétérodigital à partir d'un doigt banque est évidente, celle d'un transfert homodigital, bien qu'ayant l'avantage d'un prélèvement sur le même doigt reste rare (1,5 cas par an dans notre série). La complexité de cette reconstruction fait reculer certains patients et/ou chirurgiens qui préfèrent la simplicité et la durabilité d'une arthrodèse, voire d'une amputation.…”
unclassified
See 1 more Smart Citation